Why and How Commercial Marketing Should Promote Sufficient Consumption: A Systematic Literature Review. (September 2019) - Gossen, Maike; Ziesemer, Florence; Schrader, Ulf
Although marketing strategies are often accused of stimulating overconsumption, businesses increasingly show potential as enablers of sufficiency. The concept of sufficiency contributes to sustainable development through the absolute reduction of resources and energy used for consumption by questioning the level of demand. This study analyzes reasons and potential practices for commercial marketing to promote sufficiency through a systematic literature review of scientific publications, guided by the following research questions: Why should commercial marketing promote sufficiency? How can commercial marketing promote sufficiency? Which barriers for promoting sufficiency occur? The content-based study of 17 publications in the final review sample delivers recommendations for how to practically implement marketing for sufficiency, and theoretical considerations for strengthening the discourse within macromarketing and beyond.